KKN-PMM Regenerasi dan Inovasi Pengembangan Desa Wisata Gerabah di Penujak Praya Barat Lombok Tengah - Hamdiani, Saprini; Afandi, Muhammad Rosyad; Masloka, Michael Jonathan; Trihandayani, Baiq Nisrina; Wardani, Arifta Kusuma; Yasa, I Komang Permana; Febriansyah, Dimas Raga; Putra, Danu Eka; Baiq Maysi Dwi Alvioni3; Izzah, Bidayatul; Silva, Shelly Melsyan; Hadisaputra, Saprizal; Pahrudin, Pahrudin (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
This article discusses a community service program carried out in Penujak Village, Central Lombok, focusing on strengthening regeneration and innovation in the development of the pottery tourism village. The main problems faced include the declining interest of the younger generation in pottery, limited product innovation, and weak marketing strategies. The objectives of this program are to increase youth involvement, enhance creativity and product innovation, and expand the promotional reach of the pottery tourism village. The methods implemented include pottery socialization in schools, a Pottery Intensive Class (PIC), pottery painting competitions and art exhibitions as part of the Pottery Art Festival, website redevelopment, and the installation of cultural signboards. The results show a 78% increase in the interest of Penujak’s younger generation to try pottery-making, the establishment of digital promotional media, and the creation of broader interactions between artisans and tourists. In conclusion, this program not only contributes to the preservation of local traditions and cultural identity but also strengthens Penujak Village’s appeal as a culture-based tourism destination and opens opportunities for sustainable creative economy development within the community.